Depressive symptoms, risk of abandonment and poor adherence to treatment in patients with sensitive tuberculosis in a health center in Lima, 2016-2020 - Jonis-Jiménez, Mauro (2022)
Objective: To determine if the presence of depressive symptoms is a factor associated with abandonment or poor adherence to treatment in sensitive TB patients in a Lima health center, between 2016-2020. Materials and methods: A non-experimental, analytical, cohort, retrospective study carried out. At the Centro de Salud Materno- Infantil Buenos Aires de Villa. The information was collected from the medical records, a cohort risk estimate (Relative Risk) and levels of statistical significance were performed, with the SPSS Statistics 25 program. Results: The frequency of treatment abandonment was 18.3% (n = 28), poor adherence 42.5% (n = 65) and depression 53.6% (n = 82). Depressive symptoms were associated with treatment abandonment [RR = 2.16; 95% CI (1.01-4.60)] and poor treatment adherence [RR = 2.09; 95% CI (1.36-3.22)]. Conclusions: Depression is a risk factor significantly associated with abandonment and poor adherence to treatment in patients with sensitive tuberculosis.